Математическая модель радиоканала для MIMO-систем - Коляденко, Ю. Ю.; Коляденко, А. В. (Проблеми телекомунікацій, 2012)
A mathematical model for the channel MIMO technology, which takes into account the structural properties of the receiving antenna, the direction of arrival of signals in the main and reflected rays.
Keywords: пространственно-временное кодирование; MIMO-система; математическая модель канала; антенные решетки